Antibodies against glutamic acid decarboxylase: prevalence in neurological diseases. Issue 1 (1st July 2001) - Meinck, H-M; Faber, L; Morgenthaler, N; Seissler, J; Maile, S; Butler, M; Solimena, M; DeCamilli, P; Scherbaum, WA
Abstract : High prevalence of autoantibodies against glutamic acid decarboxylase (GAD-Ab) in stiff man syndrome (SMS) not only helps diagnosis, but also suggests immune mediated impairment of GABAergic functions. However, the presence of GAD-Ab has also been reported in other neurological syndromes. Therefore the prevalence of GAD-Ab was investigated in SMS, progressive encephalomyelitis with rigidity and myoclonus (PERM), and in other neurological diseases (OND). Serum antibodies against the GAD isoforms, GAD65 and GAD67, were investigated with radioimmunoassays in 13 patients with SMS, nine with PERM, 279 consecutive patients with OND, and in 100 normal controls. RESULTS: Prevalence of GAD65Ab was around 80% in patients with SMS/PERM compared with 5% in patients with OND and 1% in normal controls. Prevalence of GAD67Ab was 60% in SMS/PERM, 2% in patients with OND, and 1% in normal controls. Raised GAD-Ab clustered in an OND subgroup with sporadic progressive ataxia, but not in OND subgroups with recognised neuroimmunological diseases. In conclusion, increased GAD-Ab is neither a non-specific epiphenomenon of neuronal damage nor a common feature of recognised neuroimmunological disorders. In neurological diseases, GAD-Ab may be a pathogenetic agent or a marker for an ongoing autoimmune process, or both.